Antibacterial Effects of Cranberry and Lime Extracts Against Uropathogenic Escherichia coli (UPEC). - Nasution, Afrida Aryani; Mayasari, Evita; Simatupang, Maria Magdalena; Amelia, Sri; Alona, Ivana (Institute of Topical Disease Universitas Airlangga, 2025)
Urinary tract infections (UTIs) continue to increase in the number of cases and death rates every year. This increase in the number of deaths is due to an increasing trend in UTI cases in elderly patients. In Indonesia, UTI is generally caused by the uropathogenic Escherichia coli (UPEC) strain. The existence of resistant bacterial infections also triggers increased mortality in UTI patients. Several types of herbs, such as cranberries, are often used traditionally to treat UTI symptoms. Another herb that is also known to have antibacterial effects is lime. This experimental study examined the in vitro antimicrobial effects of ethanol extract of cranberry (Vaccinium macrocarpon) and ethanol extract of lime (Citrus aurantifolia L.) against UPEC by the Kirby-Bauer disc diffusion method. This study used a clinical sample obtained from an outpatient diagnosed with UTI in the Prof. dr. Chairuddin P. Lubis Universitas Sumatera Utara Hospital in March 2023. The UPEC strain was isolated and identified using the Vitek 2 Compact automated system at a local university hospital. The antimicrobial susceptibility test results indicated that the ethanol extract of cranberry did not produce an inhibition zone at concentrations of 12.5%, 25%, 50%, 60%, 70%, and 96%. The ethanol extract of lime demonstrated inhibitory zones against UPEC, with a mean diameter of 12.01 mm at a concentration of 12.5% and a mean diameter of 15.62 mm at 96%. The cranberry extract did not demonstrate an inhibitory zone against UPEC in vitro, whereas the lime extract did.